2004
DOI: 10.3748/wjg.v10.i5.676
|View full text |Cite
|
Sign up to set email alerts
|

Is the vascular endothelial growth factor messenger RNA expression in resectable hepatocellular carcinoma of prognostic value after resection

Abstract: The expression of VEGF mRNA, especially isoform VEGF(165), in HCC tissues, may play a significant and independent role in the prediction of postoperative recurrence of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In total, there were four tissue OS studies (Chow et al, 1997;Jeng et al, 2004a;Deli et al, 2005;Sheen et al, 2005), six tissue DFS studies (Jeng et al, 2004a;Sheen et al, 2005;Guo et al, 2006;Wada et al, 2006;Zhang et al, 2006;Ho et al, 2007), seven serum OS studies (Poon et al, 2001(Poon et al, , 2004a(Poon et al, , b, 2007Chao et al, 2003;Kim et al, 2004;Jeng et al, 2004b;Treiber et al, 2006), and five serum DFS studies (Poon et al, 2001(Poon et al, , 2007Chao et al, 2003;Jeng et al, 2004b;Treiber et al, 2006). Pooled HRs were then calculated for all groups.…”
Section: Summary Estimates Of Primary Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, there were four tissue OS studies (Chow et al, 1997;Jeng et al, 2004a;Deli et al, 2005;Sheen et al, 2005), six tissue DFS studies (Jeng et al, 2004a;Sheen et al, 2005;Guo et al, 2006;Wada et al, 2006;Zhang et al, 2006;Ho et al, 2007), seven serum OS studies (Poon et al, 2001(Poon et al, , 2004a(Poon et al, , b, 2007Chao et al, 2003;Kim et al, 2004;Jeng et al, 2004b;Treiber et al, 2006), and five serum DFS studies (Poon et al, 2001(Poon et al, , 2007Chao et al, 2003;Jeng et al, 2004b;Treiber et al, 2006). Pooled HRs were then calculated for all groups.…”
Section: Summary Estimates Of Primary Studiesmentioning
confidence: 99%
“…Although not entirely unexpected given the high burden of HCC in Asian populations (El-Serag, 2002), this raises a question regarding external validity of results and applicability to Western societies. However, multiple tissue (Jeng et al, 2004a;Sheen et al, 2005;Ho et al, 2007) and serum (Poon et al, 2001(Poon et al, , 2004a studies failed to find a relationship between chronic viral hepatitis status and VEGF levels. This is somewhat reassuring given the high prevalence of this liver disease aetiology in Asia.…”
Section: Test For Heterogeneitymentioning
confidence: 99%
“…Kwak et al 20 also found that tumor size was negatively correlated with immunohistochemical VEGF expression. Meanwhile, Jeng et al 21 found that the level of VEGF mRNA in HCC tissues did not significantly correlate with tumor size, cellular differentiation, capsule, daughter nodules, vascular permeation, necrosis, and hemorrhage of tumors. Ng et al 22 similarly reported that there was no statistically significant association between tumor VEGF mRNA levels and tumor size or other pathologic features.…”
Section: Pathologic Tumor Size and Vascular Endothelial Growth Factormentioning
confidence: 99%
“…42,[44][45][46][47] Moreover, high VEGF levels in HCC tissue samples are associated with rapid recurrence after resection. [48][49][50] Finally, it was recently reported that the multikinase inhibitor sorafenib increases tumoral VEGF expression, which might represent a potential road to resistance. 29,51 Hence, combination of RFA, TACE, or sorafenib with a drug that has the potential to reduce VEGF production, such as GDC-0449, might improve the efficacy of these treatment modalities.…”
Section: Discussionmentioning
confidence: 99%